Low temperature sintering of corundum powders - Sergey Veniaminovich Matrenin; Aleksandr Petrovich Ilyin; Svetlana Vladimirovna Kulyavtseva (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
Relevance of the research is caused by the necessity of profound processing of raw mineral and perfection of technology of obtaining alumoxide ceramic. The main aim of the research is to develop the activation methods of ceramic sintering based on corundum Al2O3 by mechanic treatment of powders in a planetary mill, additions of Al, Al2O3 nanopowder and TiO2 submicrom powder in a mixture, application of spark plasma sintering method. The methods: sieve analysis of a large-scale powder dispersion using the analyzer A20, x-ray phase analysis of the studied samples, hydrostatic weighting for determining a conditional density of the sintered samples, measuring microhardness of the sintered samples using microhardness tester PMT-3, measuring HRA hardness by the Rockwell hardness tester. The results. Addition of Al2O3 nanopowder in GK-5 corundum contributed to increase of sintering ceramic density and microhardness. Such activation effect is explained by the increase of interparticle contact area, which is related to Al2O3 nanopowder addition. Sintering activation is caused by high structural activity and surface energy of Al2O3 nanopowder, which are determined by crystal structure deficiency and particle small size. The most significant rise in density was observed for ceramic, containing 5…20 wt. % of Al2O3 nanowpoder. Additional activation of Al2O3 nanopowder sintering when adding aluminum nanopowder: its porosity decreased, was proved by the experiment. Sintering activation by adding Al nonopowder is explained by aluminum oxidation and phase transformation (Hedvall effect). TiO2 nanopowder additive in Al2O3 powder had the maximum activation effect: the density of sintering ceramic, containing 1,5 wt. % TiO2, achieved 3,48 g/cm3.